The nonsurgical Orthodontic correction of a Class III malocclusion Case report (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2015)
This is a case report of a patient with a skeletal Class III malocclusion and maxillary arch deficiency. The patient was treated without extraction or surgery by increasing the maxillary arch length. Protraction of the maxillary complex and A point was the result. Favorable growth of both the maxilla and the mandible resulted in a functional Class I occlusion and an improved skeletal relationship.Ban J Orthod & Dentofac Orthop, October 2012; Vol-3, No.1